Evaluation of the degree of preparedness in mass accidents and disasters of a general hospital in Attica - Farmaki, Dimitra; Kotanidou, Anastasia (Health & Research Journal, 2019)
ntroduction: Preparedness against mass and technological disasters is a fundamental obligation of contemporary hospitals. Aim: The investigation and evaluation the degree of preparedness in mass accidents and disasters of a General Hospital in Attica. Material and Methods: A cross-sectional study was conducted where the data collection was based on stratified sampling, with a self-completed questionnaire, and lasted from August to September 2015. The study sample consisted of 300 members of hospital staff. A structured questionnaire was used, where the higher the score the higher the hospital's degree of preparedness. Results: Τhe majority (58.3%) declared that the hospital has experience in dealing with the consequences of a mass disaster. However, a small percentage (21.7%) was aware of the business plans. 42.7% has been trained in first-aid care, but only 7.7% has been involved in activity of major accident and disaster. Also, 50.6% believed that the staff’s responsiveness is good/very good, while 44.3% believed that it is moderate. Hospital preparedness was rated good/very good by 46% and moderate by 41%. However, the total preparedness of hospital was 11 (± 4.7), which means moderate and in particular 41.7% of the participants scored their preparedness from 6 to 10 degrees. Furthermore,theanalysishasshownthatthehospital’sdegreeof preparednessisinfluencedbyage, professional status, responsibility, and years of experience. Conclusions: The preparedness of hospital was moderately assessed. It is therefore necessary to inform and train staff in managing major accidents and disasters.